Incidental vocabulary acquisition through watching movies with bimodal and standard subtitles: The case of L2 Swahili learners - Kwarteng, Afua Hyiah (Journal for Language Teaching, 2023)
This study aimed to identify the level of vocabulary that can be acquired by L2 Swahili learners after watching a single Swahili movie with either Swahili or English subtitles. 30 University of Ghana L2 Swahili students, ranging in age from 18-30 were divided into two groups. The groups watched the same movie in Swahili with either bimodal (BM) or standard (STD) subtitling. Those in the bimodal group watched the movie with Swahili subtitles and those in the standard group watched the movie with English subtitles. English is the medium of instruction at the University of Ghana and the official language of Ghana. Participants were tested on vocabulary taken from the movie both before and after watching the movie. They took a pre-test before watching the movie, and a post-test right after watching it, and data were analyzed using MS Excel. Results from the post-tests showed an increase in all participants’ vocabulary levels after watching the movie, with those in the standard group making statistically significant gains. The study suggests that watching a movie in L2 and visually seeing the subtitles in L1 has a greater effect on vocabulary acquisition than watching and seeing the subtitles in L2.